THE EMPLOYEE’S RIGHT TO FREEDOM OF EXPRESSION OF VIEWS IN SOCIAL MEDIA AND EMPLOYER’S CORPORATE POLICIES - Vavzhenchuk, Serhii; Zhmaka, Vladyslav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to outline the main legal issues related to limiting the right of employees to freedom of expression in social networks; highlight the methods of giving the employer’s corporate policy legal force. Research methods: synthesis, analysis, generalization, comparison, forecasting, dialectical and other methods were used to achieve the research goal. Results: the concept of "employer’s corporate policy" was analyzed using the legislation of foreign countries. Ways of giving legal force to the employer’s corporate policy are highlighted. The main provisions that should be included in the corporate policy are summarized. The relationship between corporate policy and moral rules has been studied. The practice of the European Court of Human Rights was analyzed and the relationship between corporate policy and the right to respect for private and family life and freedom of expression was investigated. Discussion: in the conditions of rapid development of information technology, it is extremely important to respond to the legal problems caused by it. Public expression of views by employees on social networks can negatively affect the business reputation and capitalization of the employer. Solving the problem of compliance with the rights of employees in the course of implementing a corporate policy on limiting the public expression of employees’ views in social networks will lead to a reduction in the risks of violation of the latter’s rights and helps to strengthen communications with employers.